1993
DOI: 10.1016/s0006-3495(93)81565-0
|View full text |Cite
|
Sign up to set email alerts
|

Human olfactory neurons respond to odor stimuli with an increase in cytoplasmic Ca2+

Abstract: The sense of smell allows terrestrial animals to collect information about the chemical nature of their environment through the detection of airborne molecules. In humans smell is believed to play an important role in protecting the organism from environmental hazards such as fire, gas leaks and spoiled food, in determining the flavor of foods, and perhaps in infant-parent bonding. In addition, the study of human olfaction is relevant to a number of medical problems that result in olfactory dysfunction, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 23 publications
3
48
0
2
Order By: Relevance
“…Odorant-stimulated olfactory tissue ranging from insects to aquatic animals and mammals showed a significant and rapid increase of IP3 at 25-50 milliseconds, followed by a rapid decline. Such a response was compatible with the physiological timeframe of a second messenger elicited through receptors that may activate a G protein (Gq or Gi) leading to stimulation of phospholipase C. In turn, IP3 was shown to increase intracellular Ca2+ by opening IP3-gated Ca2+ channels located on the plasma membrane of the olfactory neurons (Restrepo et al, 1993b (Fig. 5).…”
Section: (I) Introductionsupporting
confidence: 67%
“…Odorant-stimulated olfactory tissue ranging from insects to aquatic animals and mammals showed a significant and rapid increase of IP3 at 25-50 milliseconds, followed by a rapid decline. Such a response was compatible with the physiological timeframe of a second messenger elicited through receptors that may activate a G protein (Gq or Gi) leading to stimulation of phospholipase C. In turn, IP3 was shown to increase intracellular Ca2+ by opening IP3-gated Ca2+ channels located on the plasma membrane of the olfactory neurons (Restrepo et al, 1993b (Fig. 5).…”
Section: (I) Introductionsupporting
confidence: 67%
“…The present work reveals that salamander ORNs are also advantageous for the analysis of Ca 2ϩ signals in olfactory cilia. Thus, although previous studies have shown cytoplasmic Ca 2ϩ responses in cell bodies and dendrites of ORNs from rat (Restrepo et al, 1993b;Tareilus et al, 1995), mouse (Sato et al, 1994), man (Restrepo et al, 1993a), catfish (Restrepo et al, 1990;Restrepo and Boyle, 1991), newt (Nakamura et al, 1994), or frog (Sato et al, 1991;Lischka and Schild, 1993), this is the first to demonstrate Ca 2ϩ transients within the ORN cilia.…”
Section: Calcium Imaging Of Salamander Olfactory Ciliamentioning
confidence: 55%
“…These studies detected elevations in [Ca 2ϩ ] i resulting from stimulation with single odor ligands or odor mixtures (Restrepo et al, 1990(Restrepo et al, , 1993aRestrepo and Boyle, 1991;Sato et al, 1991Sato et al, , 1994Nakamura et al, 1994;Tareilus et al, 1995), forskolin (Sato et al, 1991;Restrepo et al, 1993b), or dialysis of ORNs with cAMP (Nakamura et al, 1994) or IP 3 (Nakamura et al, 1994;Schild et al, 1995). Despite these abundant data, studies to date have not addressed Ca 2ϩ signals in the cilia, the site of odor transduction.…”
Section: Abstract: Olfactory Receptor Neurons; Cilia; Confocal Micromentioning
confidence: 99%
“…Such an increase in [Cai] would be expected to cause a significant increase in the mean open probability for Ca2+-activated K + channels in olfactory neurons (Maue and Dionne, 1987). Indeed, addition of 5 ~M ionomycin, which causes an increase in [Cai] similar in magnitude to the odorant-induced response, causes an increase in outward current in rat and human olfactory neurons (Restrepo et al, 1993;Okada, Teeter and Restrepo, manuscript in preparation), and a decrease in extracellularly recorded spike rate in frog olfactory neurons (Frings, 1993), as would be expected if Ca 2+ causes opening of Ca2+-activated K+-channels. The diversity of the spatial distributions of the odorant-induced changes in [Cai] in different olfactory neurons has important implications for the role of Ca 2+ in olfactory transduction because Ca2+-regulated enzymes and channels are affected differently depending on their location within the cell.…”
Section: Discussionmentioning
confidence: 99%